The animator's reference book - Pardew, Les; Wolfley, Ross S.; Gale Group (Boston, Mass. Thomson Course Technology PTR, 2005)
This book is designed to assist animators with the complex challenge of creating accurate human animation. It contains synchronized photos showing a wide range of common human motion, photographed from the front, side, back, and top to provide a complete view of the action and offer a clear, frame-by-frame reference of human movement.
Chapter 1. Learning animation -- Chapter 2. The walk -- Chapter 3. Large heavy items -- Chapter 4. Walking with props -- Chapter 5. Walk variations -- Chapter 6. Sitting and standing -- Chapter 7. Lying down and getting up -- Index.
"It is intended as a resource for helping animators of all levels to understand the subtleties of actual human motion"--Introd.
Electronic reproduction.
Keywords: Animation (Cinematography) -- Handbooks, manuals, etc; Human mechanics -- Study and teaching -- Handbooks, manuals, etc; Human locomotion -- Study and teaching -- Handbooks, manuals, etc; Electronic books